Effectiveness of the CTL Model Using Liveworksheets to Improve Creative Thinking and Science Process Skills of Grade IV Elementary School Students - Azzahro, Namira Aulia; Sugandi, Asep Ikin; Puspita, Ryan Dwi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Study this aim for analyze effectiveness of the Contextual Teaching and Learning (CTL) learning model liveworksheet for increase think creative and science process skills student Grade IV Elementary School. Background from study This is low activity student in class as well as method conventional teacher - centered research method. is Research and Development (R&D) with the Borg and Gall model, which is limited to seven stages development. Subject in study This is 15 students Class IV of SDN Budi Asih for limited testing, and 36 students Class IV of SDN 4 Ciharashas for area test. Instrument data collection includes interviews, observations, and instrument tests. Validation results experts show the product is worthy used with an average percentage of practicality reached 80%. In the trial field area, class experiments show significant improvement with an N-Gain of 0.62 (medium) for think creative and 0.65 (moderate) for science process skills. The results taller compared with the class control which obtained 0.34 and 0.49 respectively. It can be concluded that effectiveness of the assisted CTL learning model embedded live worksheet​ method brainstorming can increase think creative and science process skills student grade IV elementary school.